Velocity characteristics of atrial fibrillation sources determined by electrographic flow mapping before and after catheter ablation. (1st July 2019) - Bellmann, Barbara; Zettwitz, Marit; Lin, Tina; Ruppersberg, Peter; Guttmann, Selma; Tscholl, Verena; Nagel, Patrick; Roser, Mattias; Landmesser, Ulf; Rillig, Andreas
Abstract: Background: Electrographic-Flow-(EGF)-Mapping is a novel method to identify Atrial Fibrillation (AF) drivers. Sources of excitation during AF can be characterized and monitored. Objective: The aim of this study was to evaluate the correlation between velocity of EGF around a respective AF source and its spatial variability (SV) and stability (SST). Methods: 25 patients with AF were included in this study (persistent: n = 24, long-standing persistent: n = 1; mean age 70 ± 8.3 years, male: n = 17). Focal impulse and Rotor-Mapping (FIRM) was performed in addition to pulmonary vein isolation. One-minute epochs of unipolar electrograms recorded via a 64-pole basket catheter in both atria were re-analyzed with EGF-Mapping. SST was calculated as the percentage of time in which a source was detected. Results: AF sources identified with EGF-Mapping show a wide range of SV during 1 min covering between 0.12% and 38% of the recorded basket-catheter surface. The 12 atria where the sources showed highest temporal stability (TS; between 34% and 97% of 1 min recorded) and those 12 with the lowest TS (between 11 and 20%) differed significantly in their velocities (17.8 el/s vs 12.2 el/s; p < 0.01). In 11 atria ablation caused an average decrease of TS by 47% and of velocity by 27% while SV more than doubled. Conclusion: Less stable AF-sources with high spatial variability showed reduced excitation propagation velocity while stable AF sources displayed a high average velocity in their vicinity. Importantly, catheter ablation reduced stability of sources and velocity suggesting a role of these parameters in guidance of ablation. Condensed abstract: Electrographic Flow (EGF)-Mapping is a novel method to identify Atrial Fibrillation (AF) drivers based on modeling of an electrical potential surface and subsequent flow analysis. Sources of excitation during AF can be characterized and monitored. The aim of this study was to evaluate the correlation between velocity of EGF around a respective AF source and its spatial variability and stability. Less stable AF sources with high spatial variability showed reduced excitation propagation velocity while very stable AF sources displayed a high average velocity in their vicinity. Catheter ablation reduced stability of sources and velocity. Highlights: Electrographic Flow (EGF)-Mapping is a novel method to identify Atrial Fibrillation (AF). Drivers based on modeling of an electrical potential surface and subsequent flow analysis. Sources of excitation during AF can be characterized and monitored. Less stable AF sources with high spatial variability showed reduced excitation propagation velocity. Very stable AF sources displayed a high average velocity in their vicinity. Catheter ablation reduced stability of sources and velocity.